Effect of Dimethoate Insecticide on Female Mice and Their Fetuses - Samira Sasi,; Nagia Alghoul,; Fauzia Mohamed,; Zainab ELMabrouk,; Habiba El Jaafari,; Hanain Tunsi,; Walid Saadawi,; Ragil Prastiya, (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives. Organophosphate insecticides (OPIs) including dimethoate are used in agriculture to control the insect pests, increasing the productivity, their frequent use has resulted in detrimental effects on biological systems and public health. This study aimed to evaluate the effect of dimethoate (DM) on fetuses, DNA concentration in ovarian tissues and levels of estradiol and progesterone in female mice. Methods. Female mice were divided into three groups: Group I, serve as control and was given distilled water intraperitoneally, while Group II and III were given (0.1- & 0.2-ml DM/100 ml distilled water) respectively for 7 days. Two treated females were housed with one untreated male for mating. After 7 days of the last dose, 6 female mice of each group were weighed and killed. The ovaries, uteri and liver were extracted and weighed, and ovarian hormones were measured. Also, DNA concentration in each ovary was determined. Results. The results showed a significant decrease in the weights of the liver and ovaries, the level of estradiol hormone, and DNA concentration in the ovary of treated mice as compared to those from the control group. Also, significant changes were observed in the weights of fetuses as well as the number of live fetuses. Conclusion. We found that administration of DM intraperitoneally to female mice for 7 days has influences on ovary weight, estradiol levels, and DNA concentration as well as its impact on the fetuses, therefore, it is better to use safer methods for control the pests and avoid increased use of pesticides. الخلفية والأهداف. تُستخدم المبيدات الحشرية الفوسفورية العضوية بما في ذلك الديمثويت في الزراعة للسيطرة على الآفات الحشرية، وزيادة الإنتاجية، وقد أدى استخدامها المتكرر إلى آثار ضارة على النظم البيولوجية والصحة العامة. هدفت هذه الدراسة إلى تقييم تأثير الدايمثويت على الأجنة وتركيز الحمض النووي في أنسجة المبايض ومستويات الاستراديول والبروجستيرون في إناث الفئران. طُرق الدراسة. تم تقسيم إناث الفئران إلى ثلاث مجموعات: المجموعة الأولى، كانت بمثابة مجموعة السيطرة وتم إعطاؤها ماء مقطر داخل التجويف الصفاقي، في حين أعطيت المجموعة الثانية والثالثة (0.1 و 0.2 مل 100 / DM مل ماء مقطر) على التوالي لمدة 7 أيام. تم وضع الإناث المعاملة بالدايمثويت مع الذكور غير المعاملة بنسبة (2 :1) للتزاوج. بعد 7 أيام من إعطاء الجرعة الأخيرة، تم وزن وقتل 6 إناث من كل مجموعة، تم استخراج المبايض، الرحم والكبد ووزنها وقياس هرمونات المبيض، كما تم تحديد تركيز الحمض النووي في كل مبيض. النتائج. أظهرت النتائج انخفاضاً معنوياً في أوزان الكبد، المبايض، مستوى هرمون الاستراديول وتركيز الحمض النووي في مبايض الفئران المعاملة مقارنة بالمجموعة الضابطة، كما لوحظت تغيرات كبيرة في أوزان الأجنة وكذلك عدد الأجنة الحية. الخاتمة. لقد وجدنا أن حقن DM داخل التجويف الصفاقي في إناث الفئران لمدة 7 أيام له تأثير على وزن المبيض، مستويات هرمون الاستراديول، تركيز الحمض النووي بالإضافة لتأثيراته على الأجنة، لذلك، من الأفضل استخدام طرق أكثر أمانا لمكافحة الآفات ومحاولة التقليل من الاستخدام المتزايد للمبيدات الحشرية.